2003
DOI: 10.1038/nrm1198
|View full text |Cite
|
Sign up to set email alerts
|

Titin: properties and family relationships

Abstract: In striated muscles, the rapid production of macroscopic levels of force and displacement stems directly from highly ordered and hierarchical protein organization, with the sarcomere as the elemental contractile unit. There is now a wealth of evidence indicating that the giant elastic protein titin has important roles in controlling the structure and extensibility of vertebrate muscle sarcomeres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
280
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(291 citation statements)
references
References 124 publications
3
280
0
8
Order By: Relevance
“…In the vertebrate muscle sarcomere, titin serves as a molecular ruler for sarcomere assembly and is responsible for resting elasticity of muscle (1,2) (Fig. 1A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the vertebrate muscle sarcomere, titin serves as a molecular ruler for sarcomere assembly and is responsible for resting elasticity of muscle (1,2) (Fig. 1A).…”
mentioning
confidence: 99%
“…Because titin is firmly embedded in the contractile machinery ( Fig. 1 A), its conformation and function can readily be affected by mechanical forces (1,6). The M-band, being much more compliant than the Z-disk (7,8), is ideally placed as a strain sensor (9,10).…”
mentioning
confidence: 99%
“…A significant progress in this field resulted from the studies of the third filament system of sarcomeres formed by titin and its associated proteins that extend from the Z-discs to M-lines of myofibrils (Tskhovrebova and Trinick 2003;Granzier and Labeit 2005). It was demonstrated that two giant muscle proteins, titin and nebulin/nebulette, are involved in patterning and defining the spatial dimensions of sarcomere compartments, ensuring the elasticity of myofibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Long equilibrium simulations for G5 2 and E-G5 2 were carried out using a coarse-grained native-centric model, which allowed us to follow a number of unfolding and folding reactions. In all of these simulations, the first step in the folding of both G5 2 and E-G5 2 is formation of the C-terminal β-sheet/loop motif of G5 2 (Fig. 3).…”
Section: Kinetic Experiments Reveal That Sasg Domains Fold and Unfoldmentioning
confidence: 99%
“…Some proteins function as a consequence of disorder: for example, disordered PEVK regions of titin act as an entropic spring (2), whereas in the nuclear pore complex, disordered nucleoporins provide a thick selective barrier controlling nuclear import (3). Disorder can also play other roles: it facilitates posttranslational modification and may promote allostery (4,5).…”
mentioning
confidence: 99%